Programa de subvenção ao Prêmio do Seguro Rural: uma análise da evolução na região nordeste e em Sergipe - Gois, Gislaine Santana (2022)
The Rural Insurance Premium Subsidy Program (PSR) is an agricultural policy of the Federal Government regulated by Decree nº 5.121/2004 that aims to grant economic subsidy to the rural insurance premium and, thus, promote universal access to this type of insurance. However, according to data from the PSR General Report (MAPA, 2019), it is observed that the total number of beneficiaries of the program is much higher in the South (67.6%), Southeast (19.1%) regions. and Midwest (11.8%). While the North and Northeast regions correspond to 0.9% and 1.3%, respectively. The data show that since the creation of the PSR, the Northeast has a low number of beneficiaries when compared to other regions. Thus, the general objective of this research is to analyze the factors that contribute to the Northeast region being less benefited by the PSR in the period from 2006 to 2021. The methodological procedures adopted were bibliographic research, document analysis, survey and analysis of quantitative data. It was found that Rural Credit is the main instrument of Brazilian agricultural policy and that the geographical inequality in the distribution of these resources influences the distribution of other agricultural policy instruments, as is the case of Rural Insurance in Brazil. The analysis of the evolution of Rural Insurance in Brazil (2006 to May 2022) revealed the concentration of policies in the grain category (76.08%), in which soybean production holds 57.72% of policies and corn cultivation 2nd harvest corresponds to 17.40%. There was also a concentration of rural credit and rural insurance in the South region (34% of the total volume of rural credit offered in the country in 2021 and 58.7% of the total volume subsidized in the country 2020/2021 harvest). The Northeast concentrates the largest number of rural credit agreements in the country (42% 2020/2021 Crop), but corresponds to only 8% of the total volume of rural credit applied, due to the predominance of small rural producers in this region. The Northeast has a low number of policies contracted (3533 in 2021) and, consequently, a low number of producers benefiting from the PSR (2728 in 2021), as well as the small coverage of the insured area (0.5 million hectares) and low participation in the grant (3.7% of the total grants awarded in the country in 2021). Sergipe follows the national trend and concentrates the largest number of policies in the grain category, corresponding to 92.06% (2014 to May 2022), 1st harvest corn production accounts for 99.52% of the policies contracted in the state. Thus, the unequal distribution of Rural Credit and Rural Insurance contributes to the worsening of the agrarian question. The concentration of resources destined to the cultivation of grains, especially soybeans and corn, shows that Brazilian agricultural policy is still destined to prioritize the international commodity market and large rural producers. Therefore, rural credit and rural insurance, as they are operated in Brazil, are inefficient as mechanisms to promote regional development.